Book Review: High Stakes: Children, Testing, and Failure in American Schools - Stephen A. Swindler (Journal of Research in Rural Education, 2003)
High Stakes: Children, Testing, and Failure in American Schools is the story of an academic couple's year of teaching elementary school in a poverty stricken, rural Louisiana community. Driven by their frustration with what they view as the indifference of teacher educators toward real-world schooling, Dale D. Johnson and Bonnie Johnson set out to reconnect with this world. Along the way, we learn about teaching in a high-poverty, southern rural community and the unyielding pressure from Louisiana's state standards and accountability system upon teachers.